A review on Numbered Head Together (NHT) learning model to improve biology learning outcomes - Mia Nurkanti; Ahmad Mulyadi; Ristumesi Ristumesi; Guntur Janwidi Wibowo (Universitas Ahmad Dahlan, 2021)
This study aims to analyze student learning outcomes in the NHT model on respiratory system material. This research uses library data collection methods, reading and recording research materials (library research). Data collection used is through documentation study with data collection stages by editing and organizing. Data were analyzed using inductive and deductive techniques. The results of the study: 1) student learning outcomes showed an increase in student learning outcomes using the NHT model, 2) strategies in improving learning outcomes consisted of syntax, namely numbering, asking questions, thinking together and answering questions, 3) there were student learning outcomes before the model was applied. learning is low and after the application of the NHT model has increased, 4) the effectiveness of the NHT model is effective in improving student learning outcomes, 5) the use of the NHT model can provide opportunities for students to come up with ideas of knowledge in asking and arguing.